Targeting the Cbl-b-Notch1 axis as a novel immunotherapeutic strategy to boost CD8+ T-cell responses - Monticone, Giulia; Huang, Zhi; Csibi, Fred; Leit, Silvana; Ciccone, David; Champhekar, Ameya S.; Austin, Jermaine E.; Ucar, Deniz A.; Hossain, Fokhrul; Ibba, Salome V.; Boulares, A. Hamid; Carpino, Nicholas; et al. (Frontiers in Immunology, 2022)
A critical feature of cancer is the ability to induce immunosuppression and evade immune responses. Tumor-induced immunosuppression diminishes the effectiveness of endogenous immune responses and decreases the efficacy of cancer immunotherapy. In this study, we describe a new immunosuppressive pathway in which adenosine promotes Casitas B-lineage lymphoma b (Cbl-b)-mediated Notch1 degradation, causing suppression of CD8+ T-cells effector functions. Genetic knockout and pharmacological inhibition of Cbl-b prevents Notch1 degradation in response to adenosine and reactivates its signaling. Reactivation of Notch1 results in enhanced CD8+ T-cell effector functions, anti-cancer response and resistance to immunosuppression. Our work provides evidence that targeting the Cbl-b-Notch1 axis is a novel promising strategy for cancer immunotherapy.